Examining the Role of Demographics in Campus Crime Alerts: Implications and Recommendations. (July 2018) - Pelfrey, William V.; Keener, Steven; Perkins, Michael
Colleges and universities are required by the Clery Act to issue crime alerts to members of the campus community. Issuing agencies have significant discretion in the timing and information included in crime alerts, including the perpetrator descriptors. The inclusion of perpetrator/suspect descriptions in the crime alert is intended to maximize public safety. Race descriptors may have negative consequences through the repetition of minority suspect information. To address the issue of demographic use in crime alerts, a mixed method approach was employed. A summary review of several years of crime alerts issued by a large urban university was conducted to assess the role of demographics. Qualitative data were collected through a series of focus groups and interviews addressing the balance of public safety and potential negative perceptions (perpetuated by crime alerts). Reviewed crime alerts indicate that they are largely posted for violent crimes, particularly robbery, armed robbery, and aggravated assault. Perpetrators are overwhelmingly male and largely Black. It is reasonable to question whether repeated descriptions of crime acts committed by Black males could raise, foster, or enhance negative stereotypes. Recommendations for model crime alerts and campus events are included. Consideration of stereotype impacts may influence crime alerts but circumstances and public risk may supersede these concerns.